2015
DOI: 10.1080/02699931.2015.1061481
|View full text |Cite
|
Sign up to set email alerts
|

Realistic affective forecasting: The role of personality

Abstract: Affective forecasting often drives decision making. Although affective forecasting research has often focused on identifying sources of error at the event level, the present investigation draws upon the ‘realistic paradigm’ in seeking to identify factors that similarly influence predicted and actual emotions, explaining their concordance across individuals. We hypothesized that the personality traits neuroticism and extraversion would account for variation in both predicted and actual emotional reactions to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 70 publications
0
18
0
1
Order By: Relevance
“…However, there are other individual factors, which have been shown to play a fundamental role in affective forecasting abilities. For example, personality has been found to explain 30% of the concordance between anticipated and experienced emotional experiences (Zelenski et al, 2013;Hoerger et al, 2016), and introverted as compared to extroverted individuals tend to anticipate more unpleasant emotions and less positive emotional states. Furthermore, there is evidence showing that people who are high in emotional intelligence are more accurate at encoding and predicting their emotional reactions (Dunn et al, 2007b;Hoerger et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other individual factors, which have been shown to play a fundamental role in affective forecasting abilities. For example, personality has been found to explain 30% of the concordance between anticipated and experienced emotional experiences (Zelenski et al, 2013;Hoerger et al, 2016), and introverted as compared to extroverted individuals tend to anticipate more unpleasant emotions and less positive emotional states. Furthermore, there is evidence showing that people who are high in emotional intelligence are more accurate at encoding and predicting their emotional reactions (Dunn et al, 2007b;Hoerger et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Research outside of the exercise context has described factors that have influenced the creation of affective forecasts. Specifically, affective state at the time of making the forecast [17], the timing of the event relative to when the forecast is made [18], not having enough information about the behavior [19], previous experience of the event being forecasted [20], and the personality traits of the individual [21] have all influenced affective forecasts. These studies demonstrated that these factors changed the valence of affective forecast and showed that previous experience changed the affective forecast.…”
Section: Introductionmentioning
confidence: 99%
“…The second hypothesis concerns Extraversion, a personality dimension marked by positive affect and sociability. Individuals high in Extraversion tend to have positive views about the future [ 34 , 35 ] and higher levels of emotional well-being, which may lead to more optimistic health assessments [ 33 , 36 ]. People who are high in Extraversion may underestimate their symptoms and report overly positive health [ 37 ].…”
Section: Introductionmentioning
confidence: 99%